THE STATE OF DEVELOPMENT AND RELATIONS OF COORDINATION ABILITIES OF PRIMARY SCHOOL PUPILS WHO BELONG TO SPECIAL MEDICAL GROUP - Yana Kushnir (Kazimierz Wielki University, 2015)
Kushnir Yana. The state of development and relations of coordination abilities of primary school pupils who belong to special medical group. Journal of Education, Health and Sport. 2015;5(11):441-452. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34296 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A441-452 https://pbn.nauka.gov.pl/works/672998 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 24.11.2015.   THE STATE OF DEVELOPMENT AND RELATIONS OF COORDINATION ABILITIES OF PRIMARY SCHOOL PUPILS WHO BELONG TO SPECIAL MEDICAL GROUP   Yana Kushnir   Lesya Ukrainka Eastern European National University   The results of the study show that the indices of physical development of pupils who belong to special medical group are within the age norms. The correlative relations are found between the indices of physical state of pupils. The anthropometric indices that are within the limits (r = 0,50; r = 0,81) are the most interconnected. They have somewhat fewer number of dependencies with the indices of physical conditioning and functional capacity of the organism (r = 0,35; r = 0,55). Some reverse relations between the indices that are within the limits (r = - 0,51; r = - 0,54) show the necessary of the development and improvement of coordination abilities.   Keywords: coordination, primary school pupils, special medical group, physical development, functional ability, physical conditioning.